Pharmacodynamic markers and clinical results from the phase 2 study of the SMAC mimetic birinapant in women with relapsed platinum‐resistant or ‐refractory epithelial ovarian cancer. Issue 4 (13th November 2015) - Noonan, Anne M.; Bunch, Kristen P.; Chen, Jin‐Qiu; Herrmann, Michelle A.; Lee, Jung‐Min; Kohn, Elise C.; O'Sullivan, Ciara C.; Jordan, Elizabeth; Houston, Nicole; Takebe, Naoko; Kinders, Robert J.; Cao, Liang; et al.
Abstract : BACKGROUND: Inhibitors of apoptosis proteins (IAPs) are key regulators of apoptosis and are frequently dysregulated in ovarian cancer. It was hypothesized that blocking IAPs with birinapant would increase tumor cell death and result in objective responses for women with platinum‐refractory and ‐resistant ovarian cancer. METHODS: In this phase 2, Cancer Therapy Evaluation Program–sponsored study, patients received birinapant at 47 mg/m 2 on days 1, 8, and 15 of 28‐day cycles. Pharmacokinetics were obtained during cycle 1. Plasma, peripheral blood mononuclear cells (PBMCs), and percutaneous tumor biopsy samples were collected before cycle 1 and after 6 weeks. The primary endpoint was an objective response or progression‐free survival lasting greater than 6 months in a mini‐max design. RESULTS: Eleven patients received birinapant; after this, accrual was terminated for lack of a clinical benefit. Birinapant was well tolerated, with predominantly grade 2 adverse events and 1 case of grade 3 lymphopenia. Pretreatment biopsy samples and PBMCs were collected; paired posttreatment biopsy samples and PBMCs were collected from 7 and 10 patients, respectively. There was consistent downregulation of cellular inhibitor of apoptosis protein 1 in tumors ( P = .016) and PBMCs ( P < .01). Procaspase 3 also decreased in tumors ( P = .031) and PBMCs ( P < .01); cleaved caspase 3 colocalized with H2A histone family member X (γ‐H2AX) in tumors after birinapant exposure. Peripheral T and B cells decreased significantly after treatment, but natural killer cells did not ( P = .04, P = .05, and P = .43, respectively). CONCLUSIONS: Birinapant shows consistent target suppression in vivo without single‐agent antitumor activity in this small population. Single‐agent pharmacodynamics are necessary to understand the drug's mechanism of action and set the stage for rational combination therapy. Preclinical studies are ongoing to identify optimal synergistic combinations for future clinical trials. Cancer 2016;122:588–597. © 2015 American Cancer Society . Abstract : Second mitochondria‐derived activator of caspases mimetics are promising novel anticancer agents designed to augment apoptosis. This phase 2 clinical trial has tested birinapant for ovarian cancer treatment, and it has incorporated extensive correlative studies to study the mechanism of action and pave the way for future combination clinical trials.